Silicon carbon composite material, its manufacturing method, and secondary battery
A silicon-carbon composite material with a core-shell structure and closed pores, manufactured via UV-ozone treatment and carbonization, addresses the volume expansion issue in silicon-based electrodes, achieving high capacity and stability in lithium-ion batteries.
Patent Information
- Application Number
- JP2023141745
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-12-14
- Filing Date
- 2023-08-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-08-31
AI Technical Summary
Existing silicon-based negative electrode materials for lithium-ion batteries suffer from significant volume expansion during the lithium desorption/insertion process, leading to structural instability and limited cycle life and capacity.
A silicon-carbon composite material with a core-shell structure featuring a silicon-carbon composite core and a carbon coating layer, incorporating closed pores and carbon-nitrogen bonds, is manufactured through a method involving surface modification of high molecular weight polymers with UV-ozone treatment and carbonization to enhance structural stability and conductivity.
The silicon-carbon composite material achieves high initial reversible capacity (>1900 mAh/g) and improved cycle stability (≥89.6% capacity retention after 100 cycles), effectively mitigating volume expansion and enhancing electrical conductivity.
Smart Images

Figure 0007621439000006 
Figure 0007621439000007 
Figure 0007621439000008
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of material manufacturing, and in particular to a silicon carbon composite material and a manufacturing method thereof, and a secondary battery. [Background technology]
[0002] At present, commercial lithium-ion batteries have difficulty meeting the requirements for long driving range of new energy vehicles, so there is a great need to develop battery products with high energy density and longer cycle life. At present, the negative electrode material of commercial lithium-ion batteries is mainly graphite, but the specific capacity of graphite is already close to its theoretical specific capacity, which greatly limits the further increase in energy of lithium-ion batteries. Silicon-based materials with higher theoretical specific capacity (4200mAh / g) and suitable for discharge platform have been the focus of attention in the industry. However, silicon also has obvious disadvantages, such as huge volume expansion during the lithium desorption / insertion process (theoretically can reach 300%) and easy efflorescence, which makes the active material attached to the surface of the current collector easily burst and even shatter until it loses electrical contact with the electrode and completely loses capacity.
[0003] CN102651476A discloses a method for preparing a silicon carbon composite anode material for lithium ion batteries, the silicon carbon composite anode material being graphite as a core and nano silicon as a shell, and being prepared by a method of charge adsorption of positive and negative ion surfactant in a solution. The composite anode material prepared by this technique has excellent cycle properties, and the silicon carbon composite anode material for lithium ion batteries prepared by this technique is assembled into a battery and tested, showing an initial reversible capacity of 1100mAh / g and an initial coulombic efficiency of 79.8%. However, its initial reversible capacity specific capacity is only 1100mAh / g, and its initial coulombic efficiency is low, both of which are less than 80%, which limits its practical application in view of current capacity needs.
[0004] CN108963208A discloses a method for producing silicon carbon anode material and a lithium ion battery, in which nano silicon and graphite are mixed in solid phase and sieved, then mixed in solid phase with amorphous carbon precursor and sieved, then vibrated and sintered to obtain silicon carbon anode material. This method can achieve uniform dispersion of nano silicon on the surface of graphite, and the carbon coating on the outer surface can alleviate the volume expansion caused by nano silicon during lithium desorption / insertion process. However, its first charge specific capacity is only 585mAh / g at most, which is lower than the current capacity needs.
[0005] Therefore, how to obtain a silicon negative electrode material that can effectively mitigate the volume expansion and has high specific capacity and long cycle life remains a difficult problem that needs to be urgently solved in the industry. Summary of the Invention [Problem to be solved by the invention]
[0006] In view of the above problems, the present invention provides a silicon carbon composite material, a manufacturing method thereof, and a secondary battery. The silicon carbon composite material according to the present invention can effectively mitigate the huge volume effect that occurs in the lithium desorption / insertion process of silicon, and has higher capacity and better cycle characteristics. [Means for solving the problem]
[0007] To achieve the above object, a first aspect of the present invention provides a silicon carbon composite material, comprising a silicon carbon composite core and a carbon coating layer covering the silicon carbon composite core, the silicon carbon composite core having a plurality of closed pores dispersed therein, for example at least 2, 3, 4, 5 or more closed pores. The silicon carbon composite material is in the form of particles, and may be spherical, elliptical, flat, rectangular, blocky, flattened, spherical, irregular three-dimensional, etc.
[0008] The multiple closed pores in the silicon carbon composite core of the present invention can effectively alleviate the huge volume effect generated by silicon during the lithium desorption / insertion process, and the silicon carbon composite core and the carbon coating layer can stabilize the structure of the material and increase the strength, thereby further alleviating the volume effect generated by silicon during the lithium desorption / insertion process, and ensuring that the material has better cycle properties.
[0009] In conjunction with the first embodiment, the silicon carbon composite core means that the core contains silicon material and carbon material. The carbon coating layer may be at least one layer, such as one layer, two layers, three layers, etc. Closed pores refer to pores that are formed to be closed.
[0010] In some embodiments, the silicon carbon composite core comprises a carbon filler layer and nanosilicon dispersed in the carbon filler layer and surface doped with nitrogen, where carbon nitrogen bonds are formed on the surface of the carbon filler layer and the nanosilicon.
[0011] In some embodiments, a plurality of closed pores are dispersed in the carbon filled layer, the walls of the closed pores are the carbon layer, and carbon-nitrogen bonds are formed on the surface of the carbon layer and the nanosilicon.
[0012] In some embodiments, the carbon layer has a thickness of 0.1-2.0 μm and comprises 1-10% by weight of the silicon carbon composite.
[0013] In some embodiments, the spacing between adjacent closed pores is 0.5 to 1.5 μm.
[0014] In some embodiments, the closed pores have a pore diameter of 0.5 to 2.0 μm.
[0015] In some embodiments, the silicon carbon composite satisfies the relationship (S1-S2) / S1≧50%, where S1 is the cross-sectional area of the silicon carbon composite and S2 is the sum of the areas of the closed pores in the cross-section of the silicon carbon composite.
[0016] In some embodiments, the silicon carbon composite has a total carbon content of 10-60 wt.%.
[0017] In some embodiments, the carbon coating layer has a thickness of 0.5 to 2.0 μm.
[0018] In some embodiments, the carbon coating layer comprises 1-10% by weight of the silicon carbon composite.
[0019] In some embodiments, the silicon carbon composite core has a thickness of ≧1.9 μm, such as from 1.9 to 20 μm, for example from 1.9 to 15 μm.
[0020] In some embodiments, the silicon carbon composite has an initial reversible capacity of ≧1900 mAh / g.
[0021] In some embodiments, the silicon carbon composite has an initial coulombic efficiency of ≧87.8%.
[0022] In some embodiments, the silicon carbon composite has a capacity retention of ≧89.6% after 100 cycles.
[0023] In a second aspect of the present invention, there is provided a method for producing a silicon carbon composite material, comprising steps (I) to (V).
[0024] (I) Surface modification of polymers A polymer is surface-treated with an ultraviolet-ozone device until it has oxygen-containing polar functional groups on its surface.
[0025] (II) Preparation of nanosilicon dispersion Nanosilicon and an amino-silane coupling agent are dissolved in an organic solvent and stirred to obtain a nanosilicon dispersion.
[0026] (III) Preparation of the first precursor The polymer after the surface modification treatment is added to the nanosilicon dispersion and stirred, and then spray-dried and granulated to obtain the first precursor.
[0027] (IV) Preparation of the second precursor Under a protective atmosphere, the first precursor is first heated to the softening temperature of the polymer and subjected to a first heat-holding treatment, then heated to the thermal decomposition temperature of the polymer and subjected to a second heat-holding treatment, and then heated and carbonized, and cooled to obtain a second precursor.
[0028] (V) Carbon coating The second precursor is carbon coated.
[0029] In accordance with a second aspect, the present invention provides a silicon carbon composite material produced by the above-described method for producing a silicon carbon composite material.
[0030] The method for producing a silicon carbon composite material according to the present invention has at least the following technical effects:
[0031] (1) When the polymer is surface-treated by an ultraviolet-ozone device and mixed with the nanosilicon dispersion, an amide bond is formed between the amino group in the amino-silane coupling agent and the oxygen-containing polar functional group, so that the nanosilicon particles are pre-adsorbed on the surface of the polymer to form a layer of "silicon film", and the polymer is then uniformly dispersed inside the first precursor material by spray drying. The polymer is softened at a softening temperature, and some of the polymer after softening is pyrolyzed before carbonization to form multiple closed pores, and the polymer forms the walls of the closed pores after carbonization, and the formed closed pores can effectively alleviate the huge volume effect that occurs in the lithium desorption / insertion process of silicon.
[0032] (2) After softening, some of the polymer can infiltrate between the nanosilicon particles, and can be further pyrolyzed and carbonized to form a dense silicon-carbon composite layer with the nanosilicon particles, which can stabilize the structure of the manufactured material and increase its strength, thereby further alleviating the volume effect and improving the cycle stability of the material. After carbonization, the polymer can further form carbon-nitrogen bonds with the nitrogen elements on the surface of the nanosilicon particles, which can improve the conductive properties of the material.
[0033] As the third aspect, a carbon coating layer can be formed by coating the second precursor with carbon, and the structure of the material can be stabilized by bonding this with the dense silicon-carbon composite layer.
[0034] In some embodiments, the high molecular weight polymer is slightly soluble in alcohol, poorly soluble in alcohol, or insoluble in alcohol.
[0035] In some embodiments, the polymeric polymer comprises at least one of polyvinyl chloride, polymethyl methacrylate, polystyrene, polypropylene, polyethylene terephthalate, polyetherimide, polycarbonate, cellulose acetate, polycaprolactam, and polyacrylamide.
[0036] In some embodiments, the polymer has a Dv50 of 0.5 to 5.0 μm.
[0037] In some embodiments, the softening point of the high molecular weight polymer is 100 to 300°C.
[0038] In some embodiments, the thermal decomposition temperature of the polymer is 350 to 450°C.
[0039] In some embodiments, the ultraviolet light source of the ultraviolet-ozone device is a low pressure mercury lamp.
[0040] In some embodiments, the oxygen concentration in the gas supplied to the ultraviolet light-ozone device is atmospheric oxygen concentration.
[0041] In some embodiments, the ultraviolet light of the ultraviolet-ozone device has two wavelengths, with wavelength ranges of 250-260 nm and 180-190 nm, respectively.
[0042] In some embodiments, the power of the ultraviolet light source of the ultraviolet-ozone device is 10-50W.
[0043] In some embodiments, when the ultraviolet-ozone device surface-treats the polymer, the distance between the polymer and the ultraviolet light source is 5.0 to 10.0 cm.
[0044] In some embodiments, the time for surface treatment with the ultraviolet-ozone device is 1 to 10 minutes.
[0045] In some embodiments, the nanosilicon has a Dv50 of 30-150 nm.
[0046] In some embodiments, the mass ratio of the polymer, the nanosilicon, and the amino-based silane coupling agent is (2-6):(8-12):1.
[0047] In some embodiments, the amino-based silane coupling agent comprises at least one of (3-aminopropyl)triethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane, and polyaminoalkyltrialkoxysilane.
[0048] In some embodiments, the stirring time during the preparation of the nanosilicon dispersion in step (II) is 10 to 30 minutes.
[0049] In some embodiments, the stirring rotation speed during the preparation of the nanosilicon dispersion in step (II) is 800 to 1300 r / min.
[0050] In some embodiments, in the preparation of the first precursor in step (III), the polymer after surface modification is added to the nanosilicon dispersion, and an organic solvent is added to adjust the solid content to 10-15%.
[0051] In some embodiments, the temperature of the material inlet for spray drying is 120-200°C and the temperature of the material outlet for spray drying is 70-120°C.
[0052] In some embodiments, the protective atmosphere comprises at least one of argon gas, nitrogen gas, and helium gas.
[0053] In some embodiments, the carbonization temperature is 600 to 1100°C.
[0054] In some embodiments, the first incubation treatment time is 0.1 to 1.0 hours, In some embodiments, the second incubation time is 1 to 3 hours; In some embodiments, the carbonization time is 2 to 4 hours.
[0055] In some embodiments, the second precursor is carbon coated and then post-treated, where the post-treatment includes grinding and sieving.
[0056] In some embodiments, the carbon coating comprises coating the second precursor with a carbon source, and the means of coating is liquid coating, vapor coating, or solid coating.
[0057] In the third aspect of the present invention, a silicon carbon composite material is applied to an anode material, which can meet the high cycle and low expansion requirements of the anode material by using the silicon carbon composite material as an anode active material.
[0058] In a fourth aspect of the present invention, a secondary battery is provided, comprising a positive electrode material and a negative electrode material, the negative electrode material comprising the silicon carbon composite material described above, or a silicon carbon composite material produced by the method for producing a silicon carbon composite material described above. [Brief description of the drawings]
[0059] [Figure 1] FIG. 1 is a schematic diagram of the structure of a silicon carbon composite material according to the present invention. [Diagram 2] FIG. 2 is a partial cross-sectional line scan of a single particle of the silicon carbon composite material in Example 1. [Diagram 3] FIG. 3 is a partial cross-sectional line scan of a single particle of the silicon carbon composite material in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0060] The silicon carbon composite material according to the present invention can be applied to a secondary battery as an anode active material. The secondary battery includes a cathode material and an anode material. The cathode material includes at least one of a lithium cobalt oxide-based cathode material, a lithium iron phosphate-based cathode material, a lithium nickel cobalt manganese oxide-based cathode material, and a lithium nickel cobalt aluminate-based cathode material. The silicon carbon composite material may be used independently as an anode active material, or may be mixed with other anode active materials (e.g., silicon-based materials, natural graphite, artificial graphite, soft carbon, and / or hard carbon, etc.). The secondary battery may be a lithium ion battery, a sodium ion battery, or a potassium ion battery.
[0061] 1, a silicon carbon composite material 100 according to the present invention comprises a silicon carbon composite core 10 and a carbon coating layer 30 coating the silicon carbon composite core 10, with a plurality of closed pores 50 dispersed in the silicon carbon composite core 10. The silicon carbon composite core 10 comprises a carbon filled layer 11 and nanosilicon 13 filled in the carbon filled layer 11. The closed pores 50 are dispersed in the carbon filled layer 11 and have a carbon layer 15 as a surrounding wall.
[0062] The initial reversible capacity of the silicon carbon composite is ≧1900mAh / g, for example, but not limited to, the initial reversible capacity of the silicon carbon composite is ≧1900mAh / g, 1930mAh / g, 1950mAh / g, 1970mAh / g, 1990mAh / g, 2000mAh / g, 2030mAh / g, 2060mAh / g, 2090mAh / g, 2100mAh / g. The initial coulombic efficiency of the silicon carbon composite is ≧87.8%, for example, but not limited to, the initial coulombic efficiency of the silicon carbon composite is ≧87.8%, 88.1%, 88.5%, 88.8%, 89.0%, 89.5%, 89.8%, 90.0%, 90.3%, 90.5%, 90.8%, 91.0%. The capacity retention of the silicon carbon composite after 100 cycles is ≧89.6%, for example, the capacity retention of the silicon carbon composite after 100 cycles may be ≧89.6%, 90.0%, 90.5%, 91.0%, 91.5%, 92.0%, 92.5%, 93.0%, 93.5%, 94.0%, 94.5%, 95.0%, 95.5%, 96.0%, 96.5%, 97.0%, 97.5%, 98.0%, 98.5%, 99.0%, but not limited thereto. In one technical proposal, the total carbon content of the silicon carbon composite is 10-60 wt.%. In some embodiments, the total carbon content of the silicon carbon composite is 10-55 wt.%. In other embodiments, the total carbon content of the silicon carbon composite is 20-50 wt.%. By way of example, and not limitation, the total carbon content of the silicon carbon composite may be 10 wt.%, 20 wt.%, 30 wt.%, 40 wt.%, 50 wt.%, 60 wt.%.
[0063] In one technical solution, the thickness of the silicon carbon composite core is ≧1.9 μm, for example 1.9-20 μm, for example 1.9-15 μm, 2-15 μm, 3-15 μm, 4-15 μm, 5-15 μm, 2-14 μm, 2-13 μm, 2-12 μm, 2-11 μm, 2-10 μm. In the silicon carbon composite core, the surface of the nanosilicon is doped with nitrogen, and carbon-nitrogen bonds are formed on the carbon filler layer and the surface of the nanosilicon, thereby improving the conductive properties of the material.
[0064] The wall of the closed pore is a carbon layer, and carbon-nitrogen bonds are formed on the surface of the carbon layer and the nanosilicon. The thickness of the carbon layer is 0.1-2.0 μm, for example, the thickness of the carbon layer may be 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.3 μm, 1.6 μm, 1.8 μm, 2 μm, but not limited thereto. The carbon layer occupies 1-10% by weight of the silicon carbon composite material, for example, the carbon layer occupies 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% by weight of the silicon carbon composite material, but not limited thereto. In one technical solution, the interval between adjacent closed pores is 0.5-1.5 μm, for example, 0.5-1.2 μm, for example, 0.5-1.0 μm. For example, the distance between adjacent closed pores may be, but is not limited to, 0.5 μm, 0.7 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm. In one technical solution, the diameter of the closed pores is 0.5-2.0 μm, for example, 0.5-1.5 μm, for example, 0.7-1.2 μm. For example, the diameter of the closed pores may be, but is not limited to, 0.5 μm, 0.7 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 1.9 μm, 2.0 μm.
[0065] The silicon carbon composite satisfies the relationship (S1-S2) / S1 ≧50%, ≧60%, ≧70% or ≧80%, alternatively, (S1-S2) / S1≦90%, alternatively, S2 / S1≦50%, alternatively, S2 / S1 ≧10%, ≧20%, ≧30% or ≧40%, where S1 is the cross-sectional area of the silicon carbon composite and S2 is the sum of the areas of all closed pores in the cross-section of the silicon carbon composite.
[0066] The carbon coating layer may have a thickness of 0.5 to 2.0 μm, for example, but not limited to, 0.5 μm, 0.8 μm, 1.0 μm, 1.3 μm, 1.6 μm, 1.8 μm, or 2.0 μm. The carbon coating layer may account for 1 to 10% by weight of the silicon carbon composite material, for example, but not limited to, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight of the silicon carbon composite material.
[0067] The method for producing a silicon carbon composite material according to the present invention includes steps (I) to (V).
[0068] Step (I) Surface modification of polymer It involves surface treating a high molecular weight polymer with an ultraviolet-ozone device until the polymer has oxygen-containing polar functional groups on its surface.
[0069] The polymer may be solid, slightly soluble in alcohol, poorly soluble in alcohol, or insoluble in alcohol. In one technical solution, the polymer includes at least one of polyvinyl chloride, polymethyl methacrylate, polystyrene, polypropylene, polyethylene terephthalate, polyetherimide, polycarbonate, cellulose acetate, polycaprolactam, and polyacrylamide. The surface hydrocarbon group of such a polymer can absorb ultraviolet light during surface treatment with an ultraviolet-ozone device, thereby improving the surface activity of the polymer.
[0070] In one technical solution, the Dv50 of the high molecular weight polymer is 0.5-5.0 μm, for example, the Dv50 of the high molecular weight polymer may be 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, but is not limited thereto. The softening point of the high molecular weight polymer is 100-300°C, for example, the softening point of the high molecular weight polymer may be 100°C, 120°C, 150°C, 170°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, but is not limited thereto. The thermal decomposition temperature of the high molecular weight polymer is 350 to 450°C. For example, the thermal decomposition temperature of the high molecular weight polymer may be 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, or 450°C, but is not limited thereto.
[0071] When a solid polymer is surface-treated with an ultraviolet-ozone device, the polymer surface is exposed to an active environment formed by ultraviolet-ozone, which contains a large amount of active particles, such as atomic oxygen, excited molecular oxygen, and active free radicals. Ozone is constantly generated and decomposed by irradiation with shortwave ultraviolet light of two wavelengths (wavelength ranges are 250-260 nm and 180-190 nm, respectively), and the concentrations of atomic oxygen and molecular oxygen are constantly accumulated. Atomic oxygen is O( 3 P) (produced mainly by irradiation with wavelengths of 180 to 190 nm) and O ( 1 D) (mainly produced by irradiation with wavelengths of 250-260 nm), both of which act as strong oxidizing agents on polymers, quickly oxidizing the hydrocarbon compounds on the surface of polymers. At the same time, most hydrocarbon compounds absorb ultraviolet light of two different wavelengths, improving the surface activity of the polymer.
[0072] The mechanism of ozone generation and photodecomposition is as follows: Superposition such as JPEG0007621439000001.jpg22170 allows molecular oxygen to transition from a higher energy electronic state to a lower energy electronic state.
[0073] JPEG0007621439000002.jpg5170 Repulsive excited state of O2*(3Π u ) dissociates to two ground-state oxygen atoms O( 3 P) can be formed.
[0074] O2*(3Πu)→2O( 3 P) (3) Ground state oxygen atom O( 3 P) reacts with molecular oxygen to form ozone.
[0075] JPEG0007621439000003.jpg5170Ozone is photodecomposed by irradiation with ultraviolet light of 250 to 260 nm to produce atomic oxygen O( 1D) and molecular oxygen is formed. The oxygen-containing polar functional group on the surface of the polymer treated with ultraviolet light-ozone reacts with the amino group in the silane coupling agent on the surface of the nanosilicon to form an amide bond (-CONH-), thereby realizing the nanosilicon particles to be pre-adsorbed on the surface of the polymer, which not only allows the polymer to be uniformly dispersed inside the particles during the spray granulation process, but also further improves the electrical conductivity of the silicon carbon composite material through the carbon-nitrogen bond formed during the carbonization process.
[0076] As a technical solution, the model number of the ultraviolet-ozone device may be, but is not limited to, BZD250-S, from Shenzhen Huiwo Technology Co., Ltd. The ultraviolet light source of the ultraviolet-ozone device is a low-pressure mercury lamp. The oxygen concentration in the gas supplied to the ultraviolet-ozone device is the atmospheric oxygen concentration. As a technical solution, the power of the ultraviolet light source of the ultraviolet-ozone device is 10-50W, for example, 10-30W, for example, 10-20W. For example, the power of the ultraviolet light source of the ultraviolet-ozone device may be, but is not limited to, 10W, 11W, 12W, 13W, 14W, 15W, 16W, 17W, 18W, 19W, 20W. When the ultraviolet-ozone device is used to treat a solid polymer surface, the distance between the polymer and the ultraviolet light source is 5.0-10.0 cm, for example, 6.0-9.0 cm, for example, 6.0-7.5 cm. For example, the distance between the polymer and the ultraviolet light source may be 6.0 cm, 6.1 cm, 6.2 cm, 6.3 cm, 6.4 cm, 6.5 cm, 6.6 cm, 6.7 cm, 6.8 cm, 6.9 cm, 7.0 cm, 7.1 cm, 7.2 cm, 7.3 cm, 7.4 cm, 7.5 cm, but is not limited thereto. As a technical solution, the time for surface treatment by the ultraviolet-ozone device is 1-10 min, for example, 1-8 min, for example, 1-5 min. For example, the time for surface treatment with the ultraviolet-ozone device may be, but is not limited to, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min.
[0077] Step (II) Preparation of nanosilicon dispersion The method includes dissolving nanosilicon and an amino-silane coupling agent in an organic solvent and stirring the solution to obtain a nanosilicon dispersion.
[0078] In one technical solution, the Dv50 of the nanosilicon is 30-150nm, for example 50-150nm, for example 50-130nm. For example, the Dv50 of the nanosilicon may be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, but is not limited thereto. The mass ratio of the polymer, the nanosilicon and the amino-based silane coupling agent is (2-6):(8-12):1, and for example, the mass ratio may be, but is not limited to, 2:8:1, 2:9:1, 2:10:1, 2:11:1, 2:12:1, 3:9:1, 3:10:1, 3:11:1, 3:12:1, 4:9:1, 4:10:1, 4:11:1, 4:12:1, 5:9:1, 5:10:1, 5:11:1, 5:12:1, 6:9:1, 6:10:1, 6:11:1, 6:12:1. The amino-based silane coupling agent includes at least one of (3-aminopropyl)triethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane and polyaminoalkyltrialkoxysilane.
[0079] In one technical proposal, the stirring time is 10-30 min. In one technical proposal, the stirring rotation speed is 800-1300 r / min.
[0080] In one technical solution, the polymer after surface modification is added to the nanosilicon dispersion liquid under stirring, and an organic solvent is added to adjust the solid content to 10-15%, for example, 12-15%, 14-15%. The organic solvent may be, but is not limited to, ethanol, acetone, isopropanol. For example, the organic solvent is added to adjust the solid content to 10%, 11%, 12%, 13%, 14%, 15%, but is not limited to these.
[0081] Step (III) Preparation of the first precursor The method includes adding the surface-modified polymer to a nanosilicon dispersion, stirring the mixture, and then spray-drying and granulating the mixture to obtain a first precursor.
[0082] As one technical solution, the temperature of the material supply port for spray drying is 120 to 200 ° C, for example, 120 to 170 ° C, for example, 130 to 150 ° C. As an example, the temperature of the material supply port for spray drying may be 120 ° C, 130 ° C, 140 ° C, 150 ° C, 160 ° C, 170 ° C, 180 ° C, 190 ° C, 200 ° C, but is not limited thereto. As one technical solution, the temperature of the material discharge port for spray drying is 70 to 120 ° C, for example, 70 to 100 ° C, for example, 70 to 90 ° C. As an example, the temperature of the material discharge port for spray drying may be 70 ° C, 80 ° C, 90 ° C, 100 ° C, 110 ° C, 120 ° C, but is not limited thereto.
[0083] Step (IV) Preparation of the second precursor The method includes, under a protective atmosphere, first heating the first precursor to the softening temperature of the polymer to perform a first heat-holding treatment, then heating the first precursor to the thermal decomposition temperature of the polymer to perform a second heat-holding treatment, and then heating and carbonizing the first precursor and cooling the same to obtain a second precursor.
[0084] In one technical solution, the protective atmosphere includes at least one of argon gas, nitrogen gas, and helium gas. The first heat-retaining treatment time is 0.1-1.0h, for example, the first heat-retaining treatment time may be 0.1h, 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, but is not limited thereto. The second heat-retaining treatment time is 1-3h, for example, the second heat-retaining treatment time may be 1h, 2h, 3h, but is not limited thereto. In one technical solution, the carbonization temperature is 600-1100°C, for example, 600-900°C, for example, 650-750°C. For example, the carbonization temperature may be, but is not limited to, 600° C., 650° C., 700° C., 750° C., 800° C., 850° C., 900° C., 950° C., 1000° C., 1050° C., or 1100° C. The carbonization time is 2 to 4 hours, and for example, the carbonization time may be, but is not limited to, 2 hours, 3 hours, or 4 hours.
[0085] Step (V) Carbon Coating The second precursor is carbon coated.
[0086] In one technical solution, the carbon coating is formed by coating the second precursor with a carbon source, and the coating means is liquid phase coating, gas phase coating, or solid phase coating. Of course, other coating means such as plasma may be used as long as a carbon coating layer can be formed by coating. The formed carbon coating layer may be one layer, two layers, three layers, etc. The silicon carbon composite material according to the present invention is not limited by the carbon coating means, and is not limited by the number of layers of the carbon coating layer.
[0087] As one proposed technique, the vapor coating is a chemical vapor deposition method, which may include the steps of adding a second precursor to a CVD furnace to provide a vapor-phase carbon source under a protective atmosphere and reacting to obtain a silicon carbon composite material.
[0088] In this gas-phase coating, the protective atmosphere may be at least one of argon gas, nitrogen gas, and helium gas, but is not limited thereto. The gas flow rate of the protective atmosphere is 4 to 10 L / min, and for example, the gas flow rate of the protective atmosphere may be 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, and 10 L / min, but is not limited thereto. The reaction temperature is 700 to 1100°C, and for example, the reaction temperature may be 700°C, 800°C, 900°C, 1000°C, and 1100°C, but is not limited thereto. The heating rate is 5 to 10°C / min, and for example, the heating rate may be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min, but is not limited thereto. The gas-phase carbon source includes at least one of an alkane, an alkene, and an alkyne. For example, the alkane includes at least one of methane, ethane, and propane. The alkene includes ethylene and / or propylene. The alkyne includes acetylene and / or propyne. The gas flow rate of the gas phase carbon source is 0.5-3.0 L / min, for example, the gas flow rate of the gas phase carbon source may be 0.5 / min, 1.0 L / min, 1.5 L / min, 2.0 L / min, 2.5 L / min, 3.0 L / min, but is not limited thereto. The supply time of the gas phase carbon source is 4-8 h, for example, the supply time of the gas phase carbon source may be 4 h, 5 h, 6 h, 7 h, 8 h, but is not limited thereto.
[0089] As one technical solution, the liquid phase coating may include the steps of uniformly mixing an organic carbon source, a solvent and a second precursor to obtain a mixed liquid, spray-drying the mixed liquid, and then carbonizing it to obtain a silicon carbon composite material.
[0090] In this liquid-phase coating, the organic carbon source may be at least one of polyvinyl alcohol, glucose, and sucrose, but is not limited thereto. The solvent may be at least one of water, ethanol, acetone, and isopropanol, but is not limited thereto. The temperature at which the organic carbon source dissolves in the solvent is 60 to 95°C, and for example, the temperature at the time of dissolution may be 60°C, 63°C, 65°C, 67°C, 70°C, 73°C, 75°C, 77°C, 80°C, 83°C, 86°C, 88°C, 90°C, 92°C, or 95°C, but is not limited thereto. The reaction can be accelerated by stirring during dissolution, and the stirring time may be 0.5 to 2.0h, and for example, the stirring time may be 0.5h, 0.7h, 0.9h, 1.1h, 1.3h, 1.5h, 1.7h, 1.9h, or 2.0h, but is not limited thereto. The carbonization is performed under a protective atmosphere, and the protective atmosphere includes at least one of nitrogen gas, argon gas, and helium gas. The carbonization temperature is 700 to 1100°C, and for example, the carbonization temperature may be 700°C, 800°C, 900°C, 1000°C, and 1100°C, but is not limited thereto. The carbonization time is 2 to 6h, and for example, the carbonization time may be 2h, 3h, 4h, 5h, and 6h, but is not limited thereto. The carbonization temperature rise rate is 1 to 5°C / min, and for example, the temperature rise rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, and 5°C / min, but is not limited thereto.
[0091] As one proposed technique, the solid-state coating may include a step of rapidly mixing and dispersing a solid-state carbon source and a second precursor, followed by carbonization under a protective atmosphere to obtain a silicon carbon composite material.
[0092] In this solid coating, the solid carbon source can be, but is not limited to, solid asphalt, glucose, sucrose, phenolic resin, etc. The high-speed mixing and dispersion can be carried out by a general-purpose device, and the parameters used for mixing can be normal parameters.
[0093] The temperature used during carbonization is 700 to 1100°C, and for example, the carbonization temperature may be, but is not limited to, 700°C, 800°C, 900°C, 1000°C, and 1100°C. The carbonization time is 2 to 6h, and for example, the carbonization time may be, but is not limited to, 2h, 3h, 4h, 5h, and 6h. The temperature rise rate during carbonization is 1 to 5°C / min, and for example, the temperature rise rate may be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, and 5°C / min.
[0094] In one technical solution, the second precursor is carbon-coated and then post-treated, and the post-treatment includes pulverization and sieving. The pulverization may be, but is not limited to, VC pulverization. The rotation speed used during pulverization is 500-3000 r / min. For example, the rotation speed during pulverization may be, but is not limited to, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min, 1400 r / min, 1500 r / min, 2000 r / min, 2500 r / min, and 3000 r / min. The time for grinding is 30 to 120 min, and for example, the grinding time may be, but is not limited to, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, or 120 min. The sieve used for sieving is 100 to 500 mesh, and for example, the sieve may be, but is not limited to, 100 mesh, 130 mesh, 150 mesh, 170 mesh, 200 mesh, 230 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh, or 500 mesh.
[0095] In order to better explain the objectives, technical solutions and beneficial effects of the present invention, the present invention will be further described below by means of specific examples. Note that the methods in the following implementations are intended to further interpret and explain the present invention, and should not be construed as limiting the present invention.
[0096] Example 1 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0097] (I) Surface modification of polymers 0.5 kg of polyethylene terephthalate particles are placed in an ultraviolet-ozone device, the Dv50 of the polyethylene terephthalate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polyethylene terephthalate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively, and the irradiation is performed for 5 minutes to obtain polyethylene terephthalate having oxygen-containing polar functional groups on the surface.
[0098] (II) Preparation of nanosilicon dispersion 2.0 kg of nanosilicon (Dv50 is 100 nm) and 0.20 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0099] (III) Preparation of the first precursor Add the surface-modified polyethylene terephthalate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 30 minutes. Then, spray-dry granulation (the temperature of the material supply inlet is 130°C, and the temperature of the material discharge outlet is 80°C) is performed to obtain the first precursor.
[0100] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 230°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 417°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0101] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0102] The cross-sectional line scan of the silicon carbon composite material produced is shown in FIG. 2. The silicon carbon composite material includes a silicon carbon composite core and a carbon coating layer coating the silicon carbon composite core, and the silicon carbon composite core includes a carbon filling layer and nanosilicon dispersed in the carbon filling layer. Closed pores are dispersed in the silicon carbon composite core, the spacing between the closed pores is 0.5-1.0 μm, the diameter of the closed pores is 1.5-2.0 μm, (S1-S2) / S1 is about 60%, the occupancy rate of the closed pores is higher, the closed pores are more uniformly distributed, and the sizes of the closed pores are almost the same. It was found that the total carbon content of the silicon carbon composite material is 35 wt.%, the thickness of the carbon coating layer is about 1.5 μm, the carbon coating layer accounts for 6% by weight of the silicon carbon composite material, the thickness of the silicon carbon composite core is about 8 μm, the thickness of the carbon layer is about 0.1 μm, and the carbon layer accounts for 5% by weight of the silicon carbon composite material.
[0103] Example 2 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0104] (I) Surface modification of polymers 0.5 kg of polyethylene terephthalate particles are placed in an ultraviolet-ozone device, the Dv50 of the polyethylene terephthalate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polyethylene terephthalate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 5 minutes, polyethylene terephthalate having oxygen-containing polar functional groups on the surface is obtained.
[0105] (II) Preparation of nanosilicon dispersion 1.5 kg of nanosilicon (Dv50 is 100 nm) and 0.15 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0106] (III) Preparation of the first precursor Add the surface-modified polyethylene terephthalate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 30 minutes. Then, spray-dry granulation (the temperature of the material supply inlet is 130°C, and the temperature of the material discharge outlet is 80°C) is performed to obtain the first precursor.
[0107] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 230°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 417°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0108] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0109] Example 3 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0110] (I) Surface modification of polymers 0.5 kg of polyethylene terephthalate particles are placed in an ultraviolet-ozone device, the Dv50 of the polyethylene terephthalate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polyethylene terephthalate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 5 minutes, polyethylene terephthalate having oxygen-containing polar functional groups on the surface is obtained.
[0111] (II) Preparation of nanosilicon dispersion 1.0 kg of nanosilicon (Dv50 is 100 nm) and 0.10 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is adjusted to 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0112] (III) Preparation of the first precursor Add the surface-modified polyethylene terephthalate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 30 minutes. Then, spray-dry granulation (the temperature of the material supply inlet is 130°C, and the temperature of the material discharge outlet is 80°C) is performed to obtain the first precursor.
[0113] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 230°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 417°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0114] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0115] Example 4 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0116] (I) Surface modification of polymers 0.5 kg of polycarbonate particles are placed in an ultraviolet-ozone device, the Dv50 of the polycarbonate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polycarbonate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 5 minutes, a polycarbonate having oxygen-containing polar functional groups on the surface is obtained.
[0117] (II) Preparation of nanosilicon dispersion 2.0 kg of nanosilicon (Dv50 is 100 nm) and 0.20 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0118] (III) Preparation of the first precursor Add the surface-modified polycarbonate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 30 minutes, then spray-dry granulate (the temperature of the material inlet is 130°C, and the temperature of the material outlet is 80°C) to obtain the first precursor.
[0119] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 245°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 380°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0120] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0121] Example 5 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0122] (I) Surface modification of polymers 0.5 kg of polycarbonate particles are placed in an ultraviolet-ozone device, the Dv50 of the polycarbonate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polycarbonate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 5 minutes, a polycarbonate having oxygen-containing polar functional groups on the surface is obtained.
[0123] (II) Preparation of nanosilicon dispersion 1.5 kg of nanosilicon (Dv50 is 100 nm) and 0.15 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0124] (III) Preparation of the first precursor Add the surface-modified polycarbonate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 30 minutes, then spray-dry granulate (the temperature of the material inlet is 130°C, and the temperature of the material outlet is 80°C) to obtain the first precursor.
[0125] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 245°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 380°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0126] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0127] Example 6 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0128] (I) Surface modification of polymers 0.5 kg of polycarbonate particles are placed in an ultraviolet-ozone device, the Dv50 of the polycarbonate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polycarbonate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 5 minutes, a polycarbonate having oxygen-containing polar functional groups on the surface is obtained.
[0129] (II) Preparation of nanosilicon dispersion 1.0 kg of nanosilicon (Dv50 is 100 nm) and 0.10 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is adjusted to 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0130] (III) Preparation of the first precursor Add the surface-modified polycarbonate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 30 minutes, then spray-dry granulate (the temperature of the material inlet is 130°C, and the temperature of the material outlet is 80°C) to obtain the first precursor.
[0131] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 245°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 380°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0132] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0133] Example 7 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0134] (I) Surface modification of polymers 0.5 kg of polyethylene terephthalate particles are placed in an ultraviolet-ozone device, the Dv50 of the polyethylene terephthalate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polyethylene terephthalate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 5 minutes, polyethylene terephthalate having oxygen-containing polar functional groups on the surface is obtained.
[0135] (II) Preparation of nanosilicon dispersion 2.0 kg of nanosilicon (Dv50 is 100 nm) and 0.20 kg of anilinomethyltrimethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0136] (III) Preparation of the first precursor Add the surface-modified polyethylene terephthalate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 30 minutes. Then, spray-dry granulation (the temperature of the material supply inlet is 130°C, and the temperature of the material discharge outlet is 80°C) is performed to obtain the first precursor.
[0137] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 230°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 417°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0138] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0139] Example 8 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0140] (I) Surface modification of polymers 0.5 kg of polyethylene terephthalate particles are placed in an ultraviolet-ozone device, the Dv50 of the polyethylene terephthalate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polyethylene terephthalate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 5 minutes, polyethylene terephthalate having oxygen-containing polar functional groups on the surface is obtained.
[0141] (II) Preparation of nanosilicon dispersion 2.0 kg of nanosilicon (Dv50 is 100 nm) and 0.20 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0142] (III) Preparation of the first precursor Add the surface-modified polyethylene terephthalate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 30 minutes. Then, spray-dry granulation (the temperature of the material supply inlet is 130°C, and the temperature of the material discharge outlet is 80°C) is performed to obtain the first precursor.
[0143] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 230°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 417°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0144] (V) Carbon coating PVA was weighed out and dissolved in deionized water, and stirred at 100°C for 1.5 hours to prepare a PVA solution with a mass fraction of 1.5%. The PVA solution was then mixed with the second precursor and stirred at 90°C for 1 hour to obtain a mixture. The mixture was then spray-dried and placed in a carbonization furnace where it was heated to 1100°C at a rate of 5°C / min and carbonized for 7 hours. The mixture was then allowed to cool naturally to room temperature, and was then crushed for 100 minutes using a VC crusher rotating at 800 r / min, and sieved through a 400 mesh sieve.
[0145] Example 9 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0146] (I) Surface modification of polymers 1.0 kg of polyethylene terephthalate particles are placed in an ultraviolet-ozone device, the Dv50 of the polyethylene terephthalate is 3 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polyethylene terephthalate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 5 minutes, polyethylene terephthalate having oxygen-containing polar functional groups on the surface is obtained.
[0147] (II) Preparation of nanosilicon dispersion 2.0 kg of nanosilicon (Dv50 is 120 nm) and 0.20 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 8 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0148] (III) Preparation of the first precursor Add the surface-modified polyethylene terephthalate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 13%, and stir continuously for 30 minutes, then spray-dry granulate (the temperature of the material supply inlet is 130°C, and the temperature of the material discharge outlet is 80°C) to obtain the first precursor.
[0149] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 230°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 417°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0150] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then argon gas is supplied at a gas flow rate of 4 L / min, and methane is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0151] Example 10 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0152] (I) Surface modification of polymers 0.5 kg of polyethylene terephthalate particles are placed in an ultraviolet-ozone device, the Dv50 of the polyethylene terephthalate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 30 W, and irradiation is performed under atmospheric conditions, the distance between the polyethylene terephthalate and the ultraviolet light source is 5 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 3 minutes, polyethylene terephthalate having oxygen-containing polar functional groups on the surface is obtained.
[0153] (II) Preparation of nanosilicon dispersion 2.0 kg of nanosilicon (Dv50 is 100 nm) and 0.20 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 1000 r / min for 20 minutes to obtain a nanosilicon dispersion.
[0154] (III) Preparation of the first precursor Add the surface-modified polyethylene terephthalate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 40 minutes, then spray-dry granulate (the temperature of the material supply inlet is 180°C, and the temperature of the material discharge outlet is 100°C) to obtain the first precursor.
[0155] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 230°C at a heating rate of 2°C / min throughout the entire process, where the first heat treatment is carried out for 1.0 h, then heated to 417°C, where the second heat treatment is carried out for 1.5 h, and finally heated to 1000°C, where the precursor is carbonized for 2 hours, and then cooled to room temperature to obtain the second precursor.
[0156] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 800°C at a heating rate of 3°C / min, then nitrogen gas is supplied at a gas flow rate of 5 L / min, and acetylene is supplied at a gas flow rate of 1.5 L / min. The gas supply time is 3 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1200 r / min for 40 min, and then sieved through a 400 mesh screen.
[0157] Comparative Example 1 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0158] (I) Preparation of nanosilicon dispersion 2.0 kg of nanosilicon (Dv50 is 100 nm) and 0.20 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0159] (II) Preparation of the first precursor Add polyethylene terephthalate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and continue stirring for 30 minutes, then spray-dry granulation (the temperature of the material inlet is 130°C, and the temperature of the material outlet is 80°C) to obtain the first precursor.
[0160] (III) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 230°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 417°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0161] (IV) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0162] The cross-sectional line scan of the prepared silicon carbon composite is shown in Figure 3. The silicon carbon composite in Comparative Example 1 includes a silicon carbon composite core and a carbon coating layer covering the silicon carbon composite core, and the silicon carbon composite core includes a carbon filling layer and nano silicon dispersed in the carbon filling layer. The nano silicon particles are irregularly distributed in the carbon filling layer, and some of the holes formed in the silicon carbon composite core are mutually penetrating and unevenly distributed in the silicon carbon composite, and the silicon carbon composite with this structure cannot effectively alleviate the volume effect of silicon.
[0163] Comparative Example 2 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0164] (I) Preparation of nanosilicon dispersion 2.0 kg of nanosilicon (Dv50 is 100 nm) and 0.20 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0165] (II) Preparation of the first precursor Add polycarbonate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and continue stirring for 30 minutes, then spray-dry granulation (the temperature of the material inlet is 130°C, and the temperature of the material outlet is 80°C) to obtain the first precursor.
[0166] (III) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, and is first heated to 245°C at a heating rate of 1°C / min throughout the entire process, where the first heat treatment is carried out for 0.5 hours, then heated to 380°C, where the second heat treatment is carried out for 2 hours, and finally heated to 900°C, where the precursor is carbonized for 3 hours, and then cooled to room temperature to obtain the second precursor.
[0167] (IV) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0168] Comparative Example 3 This embodiment is a method for producing a silicon carbon composite material, which includes the following steps:
[0169] (I) Surface modification of polymers 0.5 kg of polyethylene terephthalate particles are placed in an ultraviolet-ozone device, the Dv50 of the polyethylene terephthalate is 2 μm, the ultraviolet light source is a low-pressure mercury lamp with a power of 10 W, and irradiation is performed under atmospheric conditions, the distance between the polyethylene terephthalate and the ultraviolet light source is 7 cm, the ultraviolet light has two wavelengths, and the wavelengths are 254 nm and 184 nm, respectively. After irradiation for 5 minutes, polyethylene terephthalate having oxygen-containing polar functional groups on the surface is obtained.
[0170] (II) Preparation of nanosilicon dispersion 2.0 kg of nanosilicon (Dv50 is 100 nm) and 0.20 kg of (3-aminopropyl)triethoxysilane are dissolved in ethanol, mixed, and the solid content is 10 wt.%, and stirred at a rotation speed of 900 r / min for 30 minutes to obtain a nanosilicon dispersion.
[0171] (III) Preparation of the first precursor Add the surface-modified polyethylene terephthalate to the nanosilicon dispersion while stirring, add anhydrous ethanol to make the solid content of the system 15%, and stir continuously for 30 minutes. Then, spray-dry granulation (the temperature of the material supply inlet is 130°C, and the temperature of the material discharge outlet is 80°C) is performed to obtain the first precursor.
[0172] (IV) Preparation of the second precursor The first precursor is placed in a reactor under a nitrogen gas atmosphere, heated to 900°C at a heating rate of 1°C / min, carbonized for 5 hours, and then cooled to room temperature to obtain the second precursor.
[0173] (V) Carbon coating The second precursor is placed in a CVD furnace and heated to 700°C at a heating rate of 5°C / min, then nitrogen gas is supplied at a gas flow rate of 4 L / min, and acetylene is supplied at a gas flow rate of 0.5 L / min. The gas supply time is 4 h in both cases, and the precursor is naturally cooled to room temperature. Then, the precursor is ground at a speed of 1000 r / min for 60 min, and then sieved through a 400 mesh screen.
[0174] The silicon carbon composite materials produced in Examples 1 to 10 and Comparative Examples 1 to 3 were subjected to a charge / discharge characteristic test and a cycle characteristic test under the following test conditions. The test results are shown in Table 1.
[0175] (1) Charge / discharge characteristic test The silicon carbon composite materials prepared in Examples 1-10 and Comparative Examples 1-3 are mixed with polyvinylidene fluoride (a binder) and conductive agent (Super-P) in a mass ratio of 70:15:15 as active materials, and an appropriate amount of N-methylpyrrolidone (NMP) is added as a solvent to prepare a paste, which is applied to copper foil, and then vacuum dried and roll pressed to prepare a negative electrode sheet. Metallic lithium is used as the counter electrode, and 1 mol / L LiPF6 is mixed with a ternary mixed solvent of EC:DMC:EMC=1:1:1 (v / v) to form an electrolyte solution. A polypropylene microporous membrane is used as a separator, and the CR2032 button battery is assembled in a glove box filled with protective gas. The charge and discharge test of the button battery is performed in a battery test system of Wuhan LANHE Electronics Co., Ltd. Under room temperature conditions, charge and discharge at a constant current of 0.1C to 0.01V, then discharge at a constant current of 0.02C to 0.005V, and finally charge at a constant current of 0.1C to 1.5V. The capacity charged to 1.5V is the initial charge capacity, and the ratio of the initial charge capacity to the initial discharge capacity is the initial coulombic efficiency.
[0176] (2) Cycle characteristic test The silicon carbon composite materials prepared in Examples 1-10 and Comparative Examples 1-3 were mixed with graphite to prepare active materials (capacity adjusted to about 500mAh / g), and mixed with the binder aqueous dispersion of acrylonitrile multicomponent copolymer (LA132, solid content 15%) and conductive agent (Super-P) in a mass ratio of 70:10:20. An appropriate amount of water was added as a solvent to prepare a paste, which was then applied to copper foil, vacuum dried, and roll pressed to prepare a negative electrode sheet. Metallic lithium was used as the counter electrode, and 1mol / L LiPF6 was mixed with a ternary mixed solvent of EC:DMC:EMC=1:1:1 (v / v) to form an electrolyte. A polypropylene microporous membrane was used as a separator, and the CR2032 button battery was assembled in a glove box filled with inert gas. The charge / discharge test of the button battery was carried out in the battery test system of Wuhan Landen Electronics Co., Ltd. Under normal temperature conditions, the battery is charged and discharged at a constant current of 0.1C, the charge and discharge voltage is limited to 0.005 to 1.5V, and the capacity retention and expansion rate after 100 cycles are calculated.
[0177] JPEG0007621439000004.jpg33170
[0178] Table 1. Electrochemical property test results for each example and comparative example JPEG0007621439000005.jpg110170
[0179] As can be seen from the results in Table 1, the silicon carbon composite materials prepared in Examples 1 to 10 have better charge / discharge characteristics and cycle characteristics than those in Comparative Examples 1 to 3. The polymer in Comparative Examples 1 and 2 is not surface-modified by ultraviolet light-ozone, so the polymer cannot be uniformly dispersed in the nanosilicon dispersion, and uniformly distributed closed pores cannot be formed after carbonization, making it difficult to effectively alleviate the volume effect of silicon. In Comparative Example 3, no stepwise temperature increase is adopted, so the polymer mainly forms a carbon-filled layer during carbonization, making it difficult to form a closed pore structure, resulting in poor cycle characteristics.
[0180] Finally, it should be noted that the above embodiments are merely for the purpose of illustrating the technical solution of the present invention, and do not limit the scope of protection of the present invention. Although the present invention has been described in detail through preferred embodiments, the present invention is not limited to those listed in the embodiments, and as will be understood by those skilled in the art, modifications or equivalent substitutions can be made to the technical solution of the present invention without departing from the essence and scope of the technical solution of the present invention.
Claims
1. 1. A silicon carbon composite material comprising: A silicon carbon composite material comprising: a silicon carbon composite core; and a carbon coating layer coating the silicon carbon composite core, wherein a plurality of closed pores are dispersed in the silicon carbon composite core; and wherein the silicon carbon composite material satisfies the relationship (S1-S2) / S1≧50%, where S1 is a cross-sectional area of the silicon carbon composite material, and S2 is a sum of the areas of all of the closed pores in a cross section of the silicon carbon composite material.
2. The silicon carbon composite material of claim 1, characterized in that the silicon carbon composite core comprises a carbon filled layer and nanosilicon dispersed in the carbon filled layer and doped with nitrogen on its surface, and carbon-nitrogen bonds are formed on the surfaces of the carbon filled layer and the nanosilicon.
3. The silicon carbon composite material described in claim 2, characterized in that a plurality of the closed pores are dispersed in the carbon filling layer, the surrounding walls of the closed pores are carbon layers, and carbon-nitrogen bonds are formed on the surfaces of the carbon layer and the nanosilicon.
4. 4. The silicon carbon composite material according to claim 3, wherein the carbon layer has a thickness of 0.1 to 2.0 μm and accounts for 1 to 10% by weight of the silicon carbon composite material.
5. A first feature, in which the interval between adjacent closed pores is 0.5 to 1.5 μm; A second feature in which the closed pores have a pore diameter of 0.5 to 2.0 μm; A fourth feature, in which the total carbon content of the silicon carbon composite material is 10 to 60 wt. %; A fifth feature, in which the carbon coating layer has a thickness of 0.5 to 2.0 μm; The sixth feature, wherein the carbon coating layer accounts for 1 to 10% by weight of the silicon carbon composite material; The seventh feature, wherein the thickness of the silicon carbon composite core is ≧1.9 μm. An eighth feature, wherein the initial reversible capacity of the silicon carbon composite is ≧1900 mAh / g; A ninth feature, wherein the silicon carbon composite has an initial coulombic efficiency of ≧87.8%. The silicon carbon composite material according to any one of claims 1 to 3, further comprising at least one of the following characteristics: a) a capacity retention rate of the silicon carbon composite material after 100 cycles of ≧89.6%; and b) a capacity retention rate of the silicon carbon composite material after 100 cycles of ≧89.6%.
6. 1. A method for producing a silicon carbon composite material, comprising the steps of: (I) Surface modification of polymers A polymer is surface-treated with an ultraviolet-ozone device until the polymer has an oxygen-containing polar functional group on the surface; (II) Preparation of nanosilicon dispersion Nanosilicon and an amino-silane coupling agent are dissolved in an organic solvent and stirred to obtain a nanosilicon dispersion. (III) Preparation of the first precursor The polymer after the surface modification treatment is added to the nanosilicon dispersion and stirred, and then spray-dried and granulated to obtain a first precursor; (IV) Preparation of the second precursor Under a protective atmosphere, the first precursor is first heated to a softening temperature of the polymer to perform a first heat-holding treatment, then heated to a thermal decomposition temperature of the polymer to perform a second heat-holding treatment, and then heated and carbonized, and cooled to obtain a second precursor; (V) Carbon coating A method for producing a silicon carbon composite material, comprising coating the second precursor with carbon.
7. The polymer is slightly soluble in alcohol, is poorly soluble in alcohol, or is insoluble in alcohol (1); The polymer comprises at least one of polyvinyl chloride, polymethyl methacrylate, polystyrene, polypropylene, polyethylene terephthalate, polyetherimide, polycarbonate, cellulose acetate, polycaprolactam, and polyacrylamide; The polymer has a Dv50 of 0.5 to 5.0 μm (3); The softening point of the polymer is 100 to 300° C. (4). The thermal decomposition temperature of the polymer is 350 to 450° C. (5). The ultraviolet light source of the ultraviolet-ozone device is a low-pressure mercury lamp (6); The oxygen concentration in the gas supplied to the ultraviolet ozone device is the atmospheric oxygen concentration (7); The ultraviolet ray of the ultraviolet ozone device has two wavelengths, the wavelength ranges of which are 250 to 260 nm and 180 to 190 nm, respectively (8); The power of the ultraviolet light source of the ultraviolet-ozone device is 10 to 50 W. The distance between the polymer and the ultraviolet light source is 5.0 to 10.0 cm when the ultraviolet-ozone device is used to surface treat the polymer. The duration of the surface treatment using the ultraviolet-ozone device is 1 to 10 minutes (11); The nanosilicon has a Dv50 of 30 to 150 nm (12); The mass ratio of the polymer, the nanosilicon and the amino-based silane coupling agent is (2 to 6):(8 to 12):1 (13); The amino-based silane coupling agent includes at least one of (3-aminopropyl)triethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane, and polyaminoalkyltrialkoxysilane (14). The stirring time during the preparation of the nanosilicon dispersion in step (II) is 10 to 30 min (15); The stirring rotation speed during the production of the nanosilicon dispersion in step (II) is 800 to 1300 r / min (16); In the step (III), the polymer after surface modification is added to the nanosilicon dispersion, and an organic solvent is added to adjust the solid content to 10-15%. The temperature of the material supply inlet for the spray drying is 120 to 200° C., and the temperature of the material discharge outlet for the spray drying is 70 to 120° C. (18); the protective atmosphere comprising at least one of argon gas, nitrogen gas, and helium gas; The carbonization temperature is 600 to 1100° C. (20); The first heat-retaining treatment is performed for a period of 0.1 to 1.0 hours (21); The second incubation treatment is performed for 1 to 3 hours (22); The carbonization treatment time is 2 to 4 hours (23); 7. The method of claim 6, further comprising at least one of the following features: the second precursor is carbon coated and then post-processed, the post-processing including grinding and sieving (24).
8. 7. The method for producing a silicon carbon composite material according to claim 6, characterized in that the carbon coating is formed by coating the second precursor with a carbon source, and the coating means is liquid phase coating, vapor phase coating or solid phase coating.
9. A negative electrode material comprising the silicon carbon composite material according to any one of claims 1 to 4.
10. A secondary battery including a positive electrode material and a negative electrode material, A secondary battery comprising the silicon carbon composite material according to any one of claims 1 to 4 as a negative electrode material.
Citation Information
Patent Citations
Negative electrode composite material for lithium ion battery and preparation method thereof
CN110635128A
Porous nitrogen-doped silicon-based negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
CN113023734A